Self-Efficacy and Locus of Control on Performace Moderated by Organizational Culture - Surnaini Isma Yenti; Hendrik Heri Sandi (Journal of Management and Administration Provision, 2025)
This study aims to analyze the influence of Self-Efficacy and Locus of Control on Employee Performance with Organizational Culture as a Moderator at the Class I TPI Padang Immigration Office. The reason for conducting this study is the discovery of low employee performance levels through a pre-survey, as well as the importance of self-efficacy and locus of control in improving performance in the public service environment. The method used in this study is a quantitative approach with total sampling technique involving 74 respondents. To analyze the data, Structural Equation Modeling Partial Least Square (SEM-PLS) was used with the help of SmartPLS software. The findings of this study indicate that: (1) self-efficacy has a positive and significant influence on employee performance (β = 0.376, p = 0.000), (2) locus of control has a positive and significant influence on employee performance (β = 0.412, p = 0.000), (3) organizational culture positively and significantly moderates the relationship between self-efficacy and employee performance (β = 0.254, p = 0.031), (4) organizational culture positively and significantly moderates the relationship between locus of control and employee performance (β = 0.104, p = 0.000). This study also confirms Goal Setting Theory as a theoretical foundation, showing that setting clear and specific goals can increase employee motivation and performance. The results of this study provide practical contributions for the management of the Class I TPI Padang Immigration Office to set measurable and challenging goals and create an organizational culture that supports the sustainable achievement of employee performance.